Glycine Cleavage Powers Photoheterotrophic Growth of Chloroflexus aurantiacus in the Absence of H2 - He, Lian; Wang, Yaya; You, Le; Khin, Yadana; Tang, Joseph K.-H.; Tang, Yinjie J. (Frontiers in Microbiology, 2015)
Chloroflexus aurantiacus is an anoxygenic phototrophic bacterium. Its unique CO2 fixation pathway and primitive light-harvesting antenna complexes have attracted extensive research attentions. In this work, we investigated the photoheterotrophic growth of C. aurantiacus J-10-fl using acetate (at 55 oC and without H2(g)). The results indicate that glycine can promote anaerobic biomass production in a minimal medium by 3~5 folds. Via 13C-metabolite analysis, we observed that glycine was involved in serine synthesis. Instead of being used as a major carbon source, glycine was degraded to produce C1 units and NAD(P)H. Tracer experiments also suggest that photoheterotrophic cultures growing with a exogenous glycine source exhibited capabilities of assimilating CO2 via multiple routes (including the 3-hydroxypropionate pathway). Finally, glycylglycine, a commonly used culture buffer, could also release glycine via thermal or enzymatic degradation to significantly enhance photoheterotrophic growth of C. aurantiacus.